Comparación morfométrica de la columna vertebral del ocelote (Leopardus pardalis), puma (Puma concolor) y gato doméstico (Felis catus) - Sánchez, H.L. (2018)
Ocelot and puma are native American wild cats especially distributed in mountainous and forested areas. Knowledge of the bone structure of the spine is of great importance since these species are characterized by their flexibility, which gives them the agility to climb and jump with great lightness and move quickly while capturing the prey. Our goal was to perform a comparative morphometric study between the spine of ocelot, puma and domestic cat (Felis catus). Morphometric studies (linear distances) were carried out both on the isolated anatomical pieces and on their digital representation, while the geometric morphometric analysis was performed on the latter. In this study, anatomical similarities between puma and cat that may be related to their major phylogenetic relationship were found.